The Influence of Corporate Visual Identity on Brand Recognition and Recall Among Public Universities in Nairobi County, Kenya - Ong’owo, Ndiege Nicanor; Mutwiri, Isaac; Jinaro, Paul (International Journal of Research in Interdisciplinary Studies, 2025)
Corporate visual identity (CVI) is a strategic asset for organisational branding, yet its specific influence within Kenya's public higher education sector remains underexplored. This study assessed the influence of CVI on brand recognition and recall among public universities in Nairobi County, Kenya. The specific objectives were to determine the influence of the brand logo, brand colour, and brand graphics on brand recognition and recall. The study was anchored by Visual Rhetoric Theory, Visual Semiotic Theory, and Signal Theory. A convergent mixed-methods design was employed, combining quantitative surveys with qualitative interviews and content analysis. The target population comprised students, university management, and communication staff from four public universities: University of Nairobi (UoN), Technical University of Kenya (TUK), Multimedia University of Kenya (MMU), and Co-operative University of Kenya (CUK). A sample of 384 students was calculated using Cochran's formula, yielding 301 valid responses (78.4% response rate). Purposive sampling was used to select 17 staff members for interviews. Data was collected using structured questionnaires, semi-structured interview guides, and a qualitative content analysis of digital platforms during a peak communication period (July 2 – August 18, 2025). Quantitative data was analysed using descriptive statistics in SPSS, while qualitative data was analysed thematically using NVivo. The study found that the brand logo is a critical element, with 76.5% of respondents agreeing it was unique and memorable. Brand colour was highly influential, with 79.8% of respondents finding it attractive and easy to recognise. Brand graphics were perceived positively but scored relatively lower at 64.4% on consistency. Over 82% of respondents demonstrated strong brand recognition and recall. Content analysis revealed a hierarchy of CVI compliance: UoN (92.1%), MMU (83.0%), TUK (75.7%), and CUK (71.0%). The study concludes that a cohesive and consistent CVI significantly enhances brand recognition and recall. It recommends that public universities prioritise logo simplification for digital use, enforce strict colour consistency across all platforms, develop comprehensive brand manuals for graphics, and conduct regular brand audits to maintain a competitive edge in the higher education landscape.